Supplementation of carotenoids from peach palm waste (Bactris gasipaes) obtained with an ionic liquid mediated process displays kidney anti-inflammatory and antioxidant outcomes - Santamarina, Aline B. (2022)
Sustainable extraction processes based on alternative solvents to recover bioactive compounds of different raw materials have been highlighted as excellent alternatives to supply the needs of society towards a bioeconomy strategy. Little is known about the safety and biological effect of compounds extracted by these processes. In this work, carotenoids from Bactris gasipaes wastes obtained by an IL-based process were investigated in terms of safety, anti-inflammatory and, antioxidant activity in a high-fat-diet animal model on the kidney. Wistar rats were supplemented or not by carotenoids extracted with IL or VOS. The animals supplemented with carotenoids had lower weight than control and high-fat diets. In the animals supplemented with carotenoids, the group IL improved anti-inflammatory and antioxidant activity compared with carotenoids obtained by VOS. Also, the group HFD-VOS showed moderate-severe injuries on the kidney. Then, ILs could represent a novel tool for natural pigments safely applied to food industry.